2020
DOI: 10.1111/rec.13300
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reduction capacity is limited by belowground plant recovery in a 32‐year‐old created salt marsh

Abstract: Human activities have decreased global salt marsh surface area with a subsequent loss in the ecosystem functions they provide. The creation of marshes in terrestrial systems has been used to mitigate this loss in marsh cover. Although these constructed marshes may rapidly recover ecosystem structure, biogeochemical processes may be slow to recover. We compared denitrification and dissimilatory nitrate reduction to ammonium (DNRA) rates between a 32‐year‐old excavation‐created salt marsh (CON‐2) and a nearby na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
1
13
1
Order By: Relevance
“…Although we did not directly link plant activity to N cycling, previous studies have shown tight coupling between rhizosphere activity and biogeochemical processes (Lynch & Whipps 1990; Philippot et al 2009; Koop‐Jakobsen & Giblin 2010), supporting the idea that the recovery of N‐cycling in constructed marshes may be heavily dependent on primary productivity. Further, while this work and that of Tatariw et al (2021) support the notion of structure‐function coupling (Lovell 2005; Alldred & Baines 2016) in these ecosystems, functional recovery at the ecosystem scale is dependent on widespread structural recovery.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although we did not directly link plant activity to N cycling, previous studies have shown tight coupling between rhizosphere activity and biogeochemical processes (Lynch & Whipps 1990; Philippot et al 2009; Koop‐Jakobsen & Giblin 2010), supporting the idea that the recovery of N‐cycling in constructed marshes may be heavily dependent on primary productivity. Further, while this work and that of Tatariw et al (2021) support the notion of structure‐function coupling (Lovell 2005; Alldred & Baines 2016) in these ecosystems, functional recovery at the ecosystem scale is dependent on widespread structural recovery.…”
Section: Discussionsupporting
confidence: 73%
“…Our study shows that where ecosystem structure (i.e., plant biomass) has recovered in constructed marshes, N-removal and CO 2 exchange are comparable to natural marshes. Our results also suggest that biogeochemical functions are tightly coupled to the recovery of plant biomass, which has not occurred consistently across the constructed marshes (Tatariw et al 2021). Despite this spatial variability in structural and functional recovery, this study shows that constructed marshes may have comparable biogeochemical function to natural marshes where vegetation has recovered only decades after construction.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Triplicate samples were collected from each plot for nitrate reduction (i.e., denitrification, anammox, and DNRA) potential assays as described in Tatariw et al (2021). Two cores (0-5 cm, i.d.…”
Section: Nitrate Reduction Potentialsmentioning
confidence: 99%
“…Following the 2010 Deepwater Horizon (DWH) oil spill, ecosystem recovery in mixed mangrove-marsh systems was dominated by marsh vegetation (Lin and Mendelssohn, 2012;Shapiro et al, 2016), suggesting enhanced oil sensitivity in mangroves. Although oiling has a neutral (Kleinhuizen et al, 2017) or even positive (Levine et al, 2017a) effect on N removal in marsh sediments, it can lead to long-term losses in marsh N removal capacity (Hinshaw et al, 2017;Tatariw et al, 2021), highlighting a need to understand potential differences in oiling response in marshes and mangroves.…”
Section: Introductionmentioning
confidence: 99%